What does the consumer look for? An analysis of clothing market in Argentina - Belmartino, Andrea (2016)
The aim of this research is to analyze purchase decisions of textile products with brand and design. The information was gathered through a quantitative approach applied in textile stores, surveying both purchasers and non-purchasers. The study takes place in the city of Mar del Plata (Argentina). The main results indicate that the factors which influence effective decision of purchase are related to the product, such as quality and design, to the effort of the firm to gain the loyalty of customers, and to consumer characteristics.